On the Sociology of Work: Necessity, Stimuli and Interests - Zazerskis, G. (Problemos, 1979)
The article deals with the concepts of necessity, interests and stimuli for work in relation with their methodological significance for the investigation of work as a socio logical problem. The author centres on the origins and development of stimuli for work, their dependence on economic relations and the reciprocal influences. The article also deals with the essential difference of stimuli for work under capitalism and socialism.